Policy Shifts in School Education - Mukhopadhyay, Rahul; Mehendale, Archana (Voices of Teachers and Teacher Educators, 2021)
This study explores the two decades of publication of research articles related to Teacher Education through Open Distance Learning in research journals of distance education and find out the type of delivery modes used, frequency of delivery modes and the communication approaches it follows for the delivery of instructional activities. It further examines the research method, sampling techniques, tools for data collection used in the articles and also the authorship pattern of the articles. The study presented here is a basis towards understanding of the current level of research in the field of Teacher Education through ODL. Keywords: Teacher Education, Open and Distance Learning, Instructional activities, delivery modes, Communication approach, Synchronous learning approach, Asynchronous learning approach, Blended learning approach.